Key substrate recognition residues in the active site of cystathionine beta‐synthase from Toxoplasma gondii - Conter, Carolina; Favretto, Filippo; Dominici, Paola; Martinez‐Cruz, Luis Alfonso; Astegno, Alessandra (Proteins, structure, function, and bioinformatics, 2023)
Cystathionine β‐synthase (CBS) catalyzes the condensation of l ‐serine and l ‐homocysteine to give l ‐cystathionine in the transsulfuration pathway. Recently, a few O ‐acetylserine ( l ‐OAS)‐dependent CBSs (OCBSs) have been found in bacteria that can exclusively function with l ‐OAS. CBS from Toxoplasma gondii ( Tg CBS) can efficiently use both l ‐serine and l ‐OAS to form l ‐cystathionine. In this work, a series of site‐specific variants substituting S84, Y160, and Y246 with hydrophobic residues found at the same positions in OCBSs was generated to explore the roles of the hydroxyl moieties of these residues as determinants of l ‐serine/ l ‐OAS preference in Tg CBS. We found that the S84A/Y160F/Y246V triple mutant behaved like an OCBS in terms of both substrate requirements, showing β‐replacement activity only with l ‐OAS, and pH optimum, which is decreased by ~1 pH unit. Formation of a stable aminoacrylate upon reaction with l ‐serine is prevented by the triple mutation, indicating the importance of the H‐bonds between the hydroxyl groups of Y160, Y246, and S84 with l ‐serine in formation of the intermediate. Analysis of the independent effect of each mutation on Tg CBS activity and investigation of the protein–aminoacrylate complex structure allowed for the conclusion that the hydroxyl group of Y246 has a major, but not exclusive, role in controlling the l ‐serine preference by efficiently stabilizing its leaving group. These studies demonstrate that differences in substrate specificity of CBSs are controlled by natural variations in as few as three residue positions. A better understanding of substrate specificity in Tg CBS will facilitate the design of new antimicrobial compounds.